Translog Cost Function: An application for Bangladesh Agriculture - Raihana, Bilkis (Asian Accounting and Auditing Advancement, 2011)
This study is concerned with factor substitution in Bangladesh agriculture. The translog cost function is used to study both substitutability and complementarity relationships between inputs. Using homothetic structure, the Allen partial elasticities of substitution (AES) is estimated to examine the nature of factor substitution among the four inputs of land, labor, fertilizer, and irrigation. The responsiveness of input demand to input prices is explored by estimating own price and cross-price elasticities of demand. The empirical estimates indicate the existence of both substitutability and complementarity among inputs. A very high degree of substitutability between fertilizer and irrigation was found during the study period. JEL Classification Code: Q01, R10, D24, N55